State Finland Education System and Finland Education Best Pratice - Ayu Mustika Sari; Abdulah; Wiwik Maladerita; Azwar Ananda; Rusdinal; Nurhizrah Gistituati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
In the study of theory and literacy described, it can be seen about the education system in Finland, namely the following reasons: 1. The education system in Finland is flexible, making it easier for all components of education to develop teaching methods and techniques. And encourage students to be more flexible in understanding knowledge. 2. Comprehensive education for all. Financial education assistance by the government and free of charge in learning to answer the problems of people who need education as a way to improve their standard of living. 3. Inclusion-based education. Students with special needs continue to receive the same education and the same assistance from the government as well as the components of education. 4. A job as an educator who is highly valued and has a good selection makes teaching performance considered good. 5. Famous for the results of research conducted by many students and other components, making knowledge always developing.